Analysis Of Student's Mathematics Literacy Skill Through The Learning Approach Of Science, Technology, Engineering, And Mathematics (STEM) At SMA Negeri 1 Meureubo - Maisuri M; Dazrullisa D; Henra Saputra Tanjung (UMSU, 2022)
This study aims to determine students' mathematical literacy skills through a science, technology, engineering and mathematics (STEM) learning approach at SMA Negeri 1 Meureubo. This research uses qualitative research. The subjects in this study were students of class X with a total of 27 students from SMA Negeri 1 Meureubo. Data collection techniques in this study were observation, interviews, tests and validation. From the results of the study, the analysis of students' mathematical literacy skills through a science, technology, engineering and mathematics (STEM) learning approach at SMA Negeri 1 Meureubo, students' mathematical literacy skills at level 2 were included in the medium category (2.15%) as many as 12 students, while the level 2 was in the medium category (2.15%). 1 is included in the low category (0.81%) as many as 5 students.